Is Islamic Family Law Fair for Women Not Working After Divorce? - Bukido, Rosdalina; Aminah, Siti (ANTMIND YOUTH EMPOWER FOUNDATION, 2024)
Divorce often has a major impact, especially for women who do not have their own income and are financially dependent on their partners. This study aims to examine the extent to which Islamic family law in Indonesia provides protection for women who do not work after divorce. With a qualitative approach and analysis of legal documents, this study explores issues such as maintenance, the division of common property, and child custody. The study also compared the protections available in Indonesia with international standards and practices in other Muslim countries. The results of the study show that although Islamic family law in Indonesia has regulated certain protections, its implementation in the field still faces many obstacles. Women who do not work often have difficulty obtaining alimony or a fair distribution of property, especially when ex-husbands do not fulfill their obligations. In addition, there is inequality in the distribution of assets and weak legal protection for certain cases. This research highlights the importance of legal reform to strengthen enforcement mechanisms, provide legal education to women, and ensure better access to justice. With the right reforms, it is hoped that the family law system in Indonesia can be more responsive to women's needs, create true justice, and improve their welfare after divorce.